God, science, and self - Faizi, Nauman. (Montreal ; Kingston ; London ; Chicago)
ix, 166 sayfa
Keywords: “Muhammad Iqbal (d. 1938) was one of the most influential modernist Islamic thinkers of the early twentieth century. His work as a poet, politician, philosopher, and public intellectual was widely recognized in his lifetime and plays a major role in contemporary conversations about Islam, modernity, and tradition. God, Science, and Self examines the patterns of reasoning at work in Iqbal's philosophic magnum opus, arguably the most significant text of modernist Islamic philosophy, The Reconstruction of Religious Thought in Islam. Since its initial publication in 1934, The Reconstruction has left scholars in a quandary: its themes appear eclectic, and its arguments contradictory and philosophically perplexing. In this groundbreaking study, Nauman Faizi argues that the keys to demystifying the contradictions of The Reconstruction are two competing epistemologies at play within the work. Iqbal takes knowledge to be descriptive, essential, foundational, and binary, but he also takes knowledge to be performative, contextual, probabilistic, and vague. Faizi demonstrates how these approaches to knowledge shape Iqbal's claims about personhood, God, scripture, philosophy, and science. God, Science, and Self offers an original approach to interpreting Islamic thought as it crafts relationships between scriptural texts, philosophic thought, and scientific claims for modern Muslim subjects“ --